Promote collaboration skills during the COVID-19 pandemic through Predict-Observe-Explain-based Project (POEP) learning - Silfia Ilma; Mimien Henie Irawati Al-Muhdhar; Fatchur Rohman; Murni Saptasari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
It was previously found that students have low in learning collaboration, which is the learning process has not facilitated them to develop their skills. Therefore, this study aims to investigate the effects of project-based learning (PjBL), Predict-Observe-Explain (POE), and Predict-Observe-Explain based Project (POEP) on student collaboration skills in Biology education. The pretest-posttest non-equivalent control design was used and it involved 144 tenth grade students from Tarakan, Indonesia. This research was conducted from August to December 2020, while observation sheets was used to assess the student collaborations skills. The instrument used is the student collaboration skill observation sheet refers to Greenstein, 2012. The collaboration skills observation sheet has a score of 1-4 from each aspect. The aspects used are working productively, showing respect, compromise, and responsibility. Data collection in this study was carried out using WhatsApp, and Google Classroom as learning platform. The results of the analysis of covariance (ANCOVA) showed that PjBL, POE, and POEP affected their collaboration skills (p < 0.005). The LSD test result showed that PjBL, POEP, POE, and conventional learning models were significantly different in improving the skills. The POEP class had the highest posttest score, hence it can be used to improve student collaboration skills. This research contributes to providing a learning experience that empowers students' online collaboration skills.